2018
DOI: 10.1111/1462-2920.14336
|View full text |Cite
|
Sign up to set email alerts
|

Diel dynamics and coupling of heterotrophic prokaryotes and dissolved organic matter in epipelagic and mesopelagic waters of the central Red Sea

Abstract: The ecological status of an ecosystem can be approached by the taxa present but also by the size of individual organisms. In aquatic ecosystems, flow cytometry (FC) allows to study the individual size spectra and broad community composition through the evaluation of cytometric categories. The Red Sea represents a warm oligotrophic environment with a strong diel signal of vertically migrating mesopelagic fish, which feed at night at the surface and release dissolved organic carbon (DOC) at depth during day-time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 67 publications
12
17
0
Order By: Relevance
“…Regarding the vertical distribution of heterotrophic prokaryotes, we confirm the findings of two recent studies conducted at the same site as ours, focused on the interactions of bacteria with DOC stocks at the diel (García et al 2018) and seasonal scales (Calleja et al 2019). As previously reported (Calleja et al 2019;García et al 2018), LNA bacteria dominated in the epipelagic zone while HNA bacteria prevailed in the mesopelagic zone.…”
Section: Vertical Distribution Of Picoplanktonsupporting
confidence: 91%
See 1 more Smart Citation
“…Regarding the vertical distribution of heterotrophic prokaryotes, we confirm the findings of two recent studies conducted at the same site as ours, focused on the interactions of bacteria with DOC stocks at the diel (García et al 2018) and seasonal scales (Calleja et al 2019). As previously reported (Calleja et al 2019;García et al 2018), LNA bacteria dominated in the epipelagic zone while HNA bacteria prevailed in the mesopelagic zone.…”
Section: Vertical Distribution Of Picoplanktonsupporting
confidence: 91%
“…For heterotrophic prokaryotes, although our knowledge about their diversity is increasing (Ngugi et al 2012;Pearman et al 2017;Thompson et al 2017), only a few studies have investigated their vertical distribution in Red Sea waters (Calbet et al 2015;Qian et al 2011). A recent report using data collected from the same site as this study has shown that the abundance of heterotrophic bacteria can change temporally up to 3-fold within the same depth in the upper epipelagic (Calleja et al 2019;García et al 2018). Other studies conducted at that site have shown that LNA bacteria dominated in the epipelagic layer, while HNA cells were more abundant in the mesopelagic layer, indicating that each group seems to prefer different environmental conditions Calleja et al 2018).…”
Section: Introductionmentioning
confidence: 90%
“…), and in tropical waters in general (Morán et al 2017). However, likewise early observations in the Caribbean (Johnson et al 1981) recently confirmed for this site (García et al 2018), DOM concentrations displayed a coherent diel pattern suggesting different timing of production and consumption ( Fig. 1 ).…”
Section: Discussionsupporting
confidence: 81%
“…Heterotrophic prokaryotes inhabiting the Red Sea seem to challenge this view. Together with diel variations of standing stocks (García et al 2018), this study), night- and day-initiated incubations of predator-free ambient assemblages with the DOM pool available at the time of sampling yielded surprising similarities in epipelagic and mesopelagic waters. A method for estimating division rates in cyanobacteria based in changes in cell size (Hunter-Cevera et al 2014, Sosik et al 2003) was adapted to obtain independent estimates of in situ net growth rates ( Fig.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation